Dietary l -tryptophan alleviated LPS-induced intestinal barrier injury by regulating tight junctions in a Caco-2 cell monolayer model - Chen, Mengdie; Liu, Yuyu; Xiong, Shanbai; Wu, Moucheng; Li, Bin; Ruan, Zheng; Hu, Xiaobo (Food & function, 2019)
The intestinal epithelial layer forms a barrier through cell–cell tight junctions and breaking or even slightly disrupting this barrier can lead to serious pathological consequences, including infection and inflammation. Various amino acids have been shown to improve the intestinal tract, but the effect of tryptophan on the intestinal barrier has been controversial. Here, an in vitro Caco-2 cell model was built to investigate the protective and reparative effects of different concentrations of dietary l -Tryptophan ( l -Trp) on lipopolysaccharide (LPS)-induced intestinal tight junction injury. Lower concentrations (40 μM) of dietary l -Trp protected and repaired the integrity and permeability injury of the intestinal tight junction induced by LPS, while high concentrations (80 μM) may not have a positive effect. LPS-induced injury led to increased ( P < 0.05) mRNA expression of Nuclear factor-kappa B (NFκB) and Myosin light-chain kinase (MLCK), and decreased ( P < 0.05) the mRNA expression of extracellular regulated protein kinase 1/2 (ERK1/2) and Mitogen-activated protein (MAP), and the treatment of dietary l -Trp alleviated those regulations in different concentrations, which suggests that dietary l -Trp may attenuate LPS-induced injury to tight junctions via inhibiting the NFκB-MLCK signaling pathway and activating the ERK1/2-MAP signaling pathway. And the mRNA and protein expressions of claudin-1, occludin and ZO-1 in LPS-induced injury were all down-regulated to varying degrees, and dietary l -Trp weakened the down-regulation of claudin-1 ( P < 0.05) with no significant regulation of the protein expression of occludin and ZO-1 ( P > 0.05).